The Use of Code Switching and Code Meshing in Today's Youth Speech - Yules Sianipar; Gunawan Tambunsaribu (Prodi Sastra Inggris UKI, 2022)
Young people today tend to use informal language in communicating orally and in writing, in expressing themselves in front of their community or friends, but at the same time they will change their use of language into formal language when they interact with people whose position or position is above them, whether they realize it or not. The use of informal language in expressing themselves by young people is called